Prodromus of a fern flora for Bolivia. XXXIII. Blechnaceae - Smith, Alan R.; Kessler, Michael (Phytotaxa, 2018)
We provide a synopsis to the 46 species of Blechnaceae in 10 genera currently known from Bolivia, including the description of two species new to science: Blechnum tomentosum and Parablechnum wohlgemuthii. No less than 12 species are currently known only from Bolivia, making this country exceptional for the diversity of the genus.